Prevalence of alcohol abuse among workers in Italy - Venturelli, Francesco; Poscia, Andrea; Carrozzi, Giuliano; Sampaolo, Letizia; Bargellini, Annalisa; Ricciardi, Walter; Magnavita, Nicola (La Medicina del Lavoro, 2017)
Background: Unhealthy alcohol consumption among workers increases the risk of job-related injuries and reduces productivity. Therefore, preventing workplace alcohol abuse is a public health priority. Objectives: This study is based upon data collected by PASSI and aims to outline the prevalence and socio-demographic characteristics of alcohol consumption among workers in Italy. Methods: PASSI is a nationwide surveillance system that examines health-related behaviours and the degree of knowledge and adherence to the preventive interventions offered by the Italian National Health Service. Between 2010 and 2013, 101,002 telephone interviews were collected from a sample of residents aged 18-69, randomly selected from local health unit lists. Results: 45.3% of those interviewed declared to be abstemious, while 16.5% reported an unhealthy alcohol drinking, with a higher prevalence among workers than non-workers (18.0% vs 14.2%, p<0.001). Binge drinking was the most common kind of risky drinking (8.7%), followed by alcohol consumption before meals (7.3%) and heavy consumption (4.0%). Among workers, unhealthy alcohol consumption was significantly related (p<0.001) to discontinuous work (OR 1.34), male gender (OR 2.34), younger age (18-34 vs 50-69 years old, OR 2.38) and serious economic problems (OR 1.26). It was also associated with Italian citizenship (OR 1.33) and residency in the northern (OR 2.17) and central (OR 1.29) regions. Conclusions: PASSI provides reliable and updated data to develop and assess interventions in workplace health promotion.